THE ESTIMATION OF WATER QUALITY DNIPER AND DESNA IN LARGE WATER SUPPLY POINTS - Езловецкая, И. С.; Лавренчук, И. Н. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2014)
The modern of our country classification conception and standardization of water sources quality for drinking water supply are tested by example of Kyiv areas of Dniper and Desna. This conception is based on three approaches: ecological, hygienic and technological. The specific character of water quality formation is considered in summer-autumn low water for middle by water content of hydrological period. The enumeration of index, which are certain necessary for the water quality estimation, is defined. It includes the blocks of organoleptic, general sanitary chemical, hydrobiological, microbiological, parasitological, radiation safety and toxicological indexes. First the estimation of water quality of chosen drinking water surface source for Dnieper and Desna water supply point near Kyiv is done according to hygienic and ecological criteria. The list of priority indexes of water quality, which requires the immediate attention under water treatment, is established. It is defined that the coloration, content of organic and biogenic substances, dissolved oxygen, рН, abundance and biomass of phytoplankton, microbiological and some of toxicological indexes refer to the same. Results of carried out studies concerning estimation of Dnieper and Desna water quality in the district of water supply point of Kyiv can be used for development of measures concerning increase of technological operation efficiency on working constructions of Dnieper and Desna water supply stations.